Scaffold-free and label-free biofabrication technology using levitational assembly in a high magnetic field. (4th August 2020) - Parfenov, Vladislav A; Mironov, Vladimir A; van Kampen, Kenny A; Karalkin, Pavel A; Koudan, Elizaveta V; Pereira, Frederico DAS; Petrov, Stanislav V; Nezhurina, Elizaveta K; Petrov, Oleg F; Myasnikov, Maxim I; Walboomers, Frank X; Engelkamp, Hans; et al.
Abstract: The feasibility of magnetic levitational bioassembly of tissue-engineered constructs from living tissue spheroids in the presence of paramagnetic ions (i.e. Gd 3+ ) was recently demonstrated. However, Gd 3+ is relatively toxic at concentrations above 50 mM normally used to enable magnetic levitation with NdFeB-permanent magnets. Using a high magnetic field (a 50 mm-bore, 31 T Bitter magnet) at the High Field Magnet Laboratory at Radboud University in Nijmegen, The Netherlands, we performed magnetic levitational assembly of tissue constructs from living spheroids prepared from the SW1353 chondrosarcoma cell line at 0.8 mM Gd 3+ containing salt gadobutrol at 19 T magnetic field. The parameters of the levitation process were determined on the basis of polystyrene beads with a 170 μ m-diameter. To predict the theoretical possibility of assembly, a zone of stable levitation in the horizontal and vertical areas of cross sections was previously calculated. The construct from tissue spheroids partially fused after 3 h in levitation. The analysis of viability after prolonged exposure (1 h) to strong magnetic fields (up to 30 T) showed the absence of significant cytotoxicity or morphology changes in the tissue spheroids. A high magnetic field works as a temporal and removal support or so-called 'scaffield'. Thus, formative biofabrication of tissue-engineered constructs from tissue spheroids in the high magnetic field is a promising research direction